The clinical feasibility and performance of an orthogonal X-ray imaging system for image-guided radiotherapy in nasopharyngeal cancer patients: Comparison with cone-beam CT. Issue 1 (January 2016) - Zhao, Li-Rong; Zhou, Yi-Bing; Li, Guang-Hui; Li, Qi-Ming; Yang, Ding-Qiang; Li, Han-Xu; Wan, Jiu-Qing; Sun, Jian-Guo
Highlights: To investigate setup discrepancies measured between XGS-10 and CBCT. The results indicate a reasonably good agreement between the two systems. XGS-10 represents a potentially competitive alternative to CBCT for clinical use. Abstract: The demand for greater accuracy of intensity-modulated radiotherapy (IMRT) has driven the development of more advanced verification systems for image-guided radiotherapy (IGRT). The purpose of this study is to investigate setup discrepancies measured between an orthogonal X-ray guidance system (XGS-10) and cone-beam computed tomography (CBCT) of Varian in the IMRT of patients with nasopharyngeal cancer (NPC). The setup errors measured by XGS-10 and CBCT at the treatment unit with respect to the planning CTs were recorded for 30 patients with NPC. The differences in residual setup errors between XGS-10 system and CBCT were computed and quantitatively analyzed. The time of image acquisition and image registration was recorded. The radiation doses delivered by CBCT and XGS-10 were measured using PTW0.6CC ionization chambers and a water phantom. The differences between setup errors measured by the XGS-10 system and CBCT were generally <1.5 mm for translations, indicating a reasonably good agreement between the two systems for patients with NPC in the translation directions of A-P ( P = 0.856), L-R ( P = 0.856) and S-I ( P = 0.765). Moreover, compared with CBCT, XGS-10 took much shorter image acquisition and registration time ( P < 0.001) and delivered only a small fraction of extra radiation dose to the patients ( P < 0.001). These results indicate that XGS-10 offers high localization accuracy similar to CBCT and additional benefits including prompt imaging process, low imaging radiation exposure, real time monitoring, which therefore represents a potential attractive alternative to CBCT for clinical use.